Collective Leadership Model in Improving the Target of Development of Islamic Boarding School Educational Institutions: Model Kepemimpinan Kolektif Dalam Meningkatkan Target Pengembangan Lembaga Pendidikan Pondok Pesantren - Choiroer Rofiq; Yayuk Fauziyah (Universitas Muhammadiyah Sidoarjo, 2021)
The collective leadership model is very influential in the implementation of the development of educational institutions, basically the implementation of this collective leadership model is the division of tasks and positions as a whole with the shared authority and responsibility.This study describes the collective leadership model in increasing the target for the development of the An Nur Penatarsewu Islamic boarding school Tanggulangin Sidoarjo educational institution, the focus of the research is the collective leadership model, its implementation,